Malaria prevention strategies - Von Seidlein, L (Elsevier, 2016)
Substantial gains have been made in the control of malaria; in many regions malaria has reached historically low prevalence. Still the global malaria burden remains unacceptably high and the spread of antimalarial and insecticide resistance threatens a resurgence.